The Effect Of Problem Solving Learning Model Containing Science Literacy on Students’ Learning Competencies at Junior High School 29 Padang - Yayat Mutia Ardi; Rahmawati Rahmawati; Irma Leilani Eka Putri; Syamsurizal Syamsurizal (Universitas Negeri Padang, 2019)
The research problem at Junior High School 29 Padang is the science learning process that takes place centered on the teacher, the low learning competency of the students, has not used a learning model that contains sains literacy, and low scientific literacy skills. Efforts that can be done are applying the problem solving learning model with scientific literacy. This research was conducted at Junior High School 29 Padang in material of KD 3.6 about additives and addictive substance. This research is an experimental research using the Randomized Control Group Posttest Only Design. The study population was all grade VIII students of Junior High School 29 Padang. Sampling was taken by using purposive sampling technique. Class VIII.3 as the experimental class and class VIII.5 as the control class. The instruments used in the form of posttest questions, observation sheets. The research instrument used was a test of learning outcomes. The research instrument used was a test of learning outcomes. The results of the t test were known that in the knowledge competency tcount> t table (3,02>1.67). the attitude competency tcount> t table (5.38>1.67) and the skills competency tcount> t table (4,39>1.67). This showed that the hypothesis was accepted. So, it can be concluded that the application of a problem solving model with scientific literacy on additives and addictive substance can improve the competency of knowledge, attitudes, and skills of Junior High School 29 Padan students.